TRAVEL PATTERN WISATAWAN SELAMA PANDEMI COVID-19 - Retnaningtyas Susanti; sulis purwanto; Sukma Yudistira; Yuke Permata Lisna (Fakultas Pariwisata dan Perhotelan Universitas Negeri Padang, 2021)
The COVID-19 pandemic that has hit the world, including Indonesia, has had a crucial influence on the tourism industry. It is undeniable that the tourism industry in Indonesia seems to be in suspended animation due to unpreparedness for this disaster. From the supply side, tourism entrepreneurs are overwhelmed because of the absence of visits due to flight closures, travel minimization, and strict rules regarding the closure of tourist attractions during 2019. From the demand side, the community's need for tourism remains high, interest in traveling is even greater after one year